DINAMIKA POLITIK DALAM PEMBAHASAN DAN PERSETUJUAN BERSAMA RANCANGAN PERATURAN DAERAH (RANPERDA) RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH (RPJMD) KABUPATEN BENGKALIS TAHUN 2016-2021 - Ramadhan, Ardiansyah; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The Regional Medium Term Development Plan (RPJMD) is an official regional planning document that is in force within the next 5 (five) years of the elected head of the regional administration. The steps taken to establish the RPJMD is to discuss and approve the legislative with the executive. Based on this matter then formulated a problem in this research are: How the dynamics of politics in the discussion and mutual consent Proposed Regional Regulation RPJMD Bengkalis District Year 2016-2021.The purpose of this study to determine the dynamics that occurred in the process of discussion and mutual consent with Proposed Regional Regulation RPJMD Bengkalis District Year 2016-2021. This research method using qualitative approach with descriptive research type.The results of the research are as follows: First, the delay of Proposed Regional Regulation RPMMD determination of Bengkalis Regency caused by the handover of Proposed Regional Regulation RPJMD very close to the time limit given and 4 (four) fractions request to postpone the discussion Proposed Regional Regulation RPJMD. Secondly, the regional head does not propose general policies and regional medium-term development programs and indicate the priority program plan that accompanied the funding needs to the Regional House of Representatives (DPRD) for discussion and agreement. Third, there is a difference of vision of RPJMD with the vision of bupati when running and being registered at the General Elections Commission (KPU). After going through the various stages, finally the discussion Proposed Regional Regulation RPJMD completed and agreed together to then be established into a Regional Regulation.Keywords: Mutual Consent, Regional Medium Term Development Plan, Proposed Regional Regulation.